Absencja pracownicza jako ciężkie naruszenie podstawowych obowiązków pracowniczych - Omieczyńska, Sandra; Pietraszuk, Rafał (Kortowski Przegląd Prawniczy, 2022)
The issue of the employee’s absence from the workplace while he was obliged to perform work has been repeatedly considered in the light of basic employee duties, among which there is the obligation to observe the agreed time and schedule of work and the obligation to care for the welfare of the workplace. Judicature, considering the issues related to the employee’s absence, developed the thesis according to which the unjustified absence, resulting from willful misconduct or gross negligence of the employee, constitutes a serious violation of basic employee obligations, which in turn may lead to the termination of the employment contract pursuant to art. 52 of the Labor Code. In addition, unjustified and arbitrary leaving the workplace despite the order to work overtime and the exercise of the right to leave on demand despite justified objection, in accordance with the developed line of jurisprudence, may also constitute the basis for terminating the employment contract without notice due to the employee’s fault.